Individual-Based Modeling Approach to Assessment of the Impacts of Landscape Complexity and Climate on Dispersion, Detectability and Fate of Incipient Medfly Populations - Lux, Slawomir A. (Frontiers in Physiology, 2018)
The objective of the presented study was to demonstrate the potential of a bottom-up ‘ethological’ approach and individual-based model of Markov-like stochastic processes, employed to gain insights into the factors driving behaviour and fate of the invasive propagule, which determine the initial stages of pest invasion and ‘cryptic’ existence of the localised, ultra-low density incipient pest populations. The applied model, PESTonFARM, is driven by the parameters derived directly from the behaviour and biology of the target insect species, and spatiotemporal traits of the local terrain and climate. The model projections are actively generated by behaviour of the primary causative actors of the invasion processes - individual ‘virtual’ insects - members of the initial propagules or incipient populations. Algorithms of the model were adjusted to reflect behaviour and ecology of the Mediterranean fruit fly, Ceratitis capitata, used as a case-example in the presented study. The model was parametrized based on compiled published experimental information about C. capitata behaviour and development, and validated using published data from dispersion and trapping studies. The model reliably simulated behaviour, development and dispersion of individual members of an invasive cohort, and allowed to quantify pest establishment and detection chances in landscapes of varying spatiotemporal complexity, host availability and climates. The results support the common view that, under optimal conditions (farmland with continuous fruit availability and suitable climate), even a single propagule of medium size (100 females) usually results in pest establishment and detection within the first year post-invasion. The results demonstrate, however, that under specific sub-optimal conditions determined by the local climate, weather fluctuations and landscape topography (e.g. sub-urban), the incipient cryptic populations may occasionally continue for several generations, and remain undetected by typical pest surveillance grids for the periods extending beyond two-years post-invasion.